Formation and Optical Properties of Brown Carbon from Small alpha-Dicarbonyls and Amines - Marrero-Ortiz, W.; Hu, M.; Du, Z. F.; Ji, Y. M.; Wang, Y. J.; Guo, S.; Y. Lin; Gomez-Hermandez, M.; Peng, J. F.; Li, Y. X.; Secrest, J.; Zamora, M. L.; et al. (Environmental Science & Technology, 2019)
Brown Carbon (BrC) aerosols scatter and absorb solar radiation, directly affecting the Earth's radiative budget. However, considerable uncertainty exists concerning the chemical mechanism leading to BrC formation and their optical properties. In this work, BrC particles were prepared from mixtures of small alpha-dicarbonyls (glyoxal and methylglyoxal) and amines (methylamine, dimethylamine, and trimethylamine). The absorption and scattering of BrC particles were measured using a photoacoustic extinctometer (405 and 532 nm), and the chemical composition of the alpha-dicarbonyl-amine mixtures was analyzed using orbitrap-mass spectrometry and thermal desorption-ion drift-chemical ionization mass spectrometry. The single scattering albedo for methylglyoxal-amine mixtures is smaller than that of glyoxal-amine mixtures and increases with the methyl substitution of amines. The mass absorption cross-section for methylglyoxal-amine mixtures is two times higher at 405 nm wavelength than that at 532 nm wavelength. The derived refractive indexes at the 405 nm wavelength are 1.40-1.64 for the real part and 0.002-0.195 for the imaginary part. Composition analysis in the alpha-dicarbonyl-amine mixtures reveals N-heterocycles as the dominant products, which are formed via multiple steps involving nucleophilic attack, steric hindrance, and dipole dipole interaction between alpha-dicarbonyls and amines. BrC aerosols, if formed from the particle-phase reaction of methylglyoxal with methylamine, likely contribute to atmospheric warming.
Keywords: absorbing aerosols; cavity ring; chemistry; glyoxal; light-absorption; methylglyoxal; particles; products; refractive-index; spectral dependence